The effects of bend radius on flow around a configuration of bendway weirs: insight from a numerical model - Hogan, Taylor, author; Thornton, Christopher, advisor; Ettema, Robert, advisor; Williams, John, committee member (Colorado State University. Libraries, 2019)
Bendway weirs have been used and refined for decades by hydraulic engineers to control thalweg location within alluvial rivers and to decrease flow velocity along the outer bank of channel bends. Although these structures have been used in a variety of applications, there are still a wide range of acceptable design parameters that vary in accordance with the specific design methodology being used. Since the early 2000s, Colorado State University's Hydraulics Lab has assisted The U.S Bureau of Reclamation (USBR) in refining the design of bendway weirs and similar in-stream rock structures. During this period of time, Colorado State University and The USBR have utilized hydraulic and numerical models to develop systematic design guidelines for bendway weirs and other in-stream rock structures. Hydraulic modeling has also provided a large database of velocity and water surface measurements that have been used to calibrate and validate subsequent numerical models. The partnership between Colorado State University and the USBR has led to design recommendations and equations in which the effect of many variables and their sensitivity in overall bendway weir design has been identified. This study investigates the parameter radius of curvature over channel top width, Rc/Tw, and its effect on the flow field around bendway weirs, as its significance in bendway weir design is not well known. To investigate the effects of Rc/Tw on the bendway weir flow field, the 2D numerical model SRH-2D was used in conjunction with AutoCAD Civil3D software. The SRH-2D model was created using the bathymetry of the hydraulic model and then also calibrated and validated using data collected in the hydraulic model. AutoCAD Civil3D was used to create four different bend radii while holding Tw constant, representing Rc/Tw values between 3.0 and 8.0 which are typical of the Middle Rio Grande that the hydraulic model represented. Two additional trapezoidal channel models were also created to isolate the possible effects from specific channel geometry on the bendway weir flow field comparisons. 2D numerical modeling results revealed that the bend radius of curvature had negligible effect on the bendway weir flow field. Velocity patterns in the trapezoidal and native bathymetry channels changed negligibly in location and magnitude across varying bend radii. Cross-sectional velocity distributions were also evaluated and showed that the inner and middle third lateral sections of the channel showed the same (within fractions of a percent) velocity increase after the installation of bendway weirs. The outer fifth of the channel resulted in 6% velocity decrease only varying approximately 0.1% between bend radii. Overall numerical modeling results showed that the bendway weir flow field was negligibly affected by the bend radius of curvature, Rc.
Keywords: change of bend radius; bendway weirs; SRH-2D